Intentional coronary revascularization versus conservative therapy in patients after peripheral artery revascularization due to critical limb ischemia: the INCORPORATE trial - Toth, Gabor G; Brodmann, Marianne; Kanoun Schnur, Sadeek S; Bartus, Stanislaw; Vrsalovic, Mislav; Krestianinov, Oleg; Kala, Petr; Bil, Jacek; Gil, Robert; Kanovsky, Jan; Di Serafino, Luigi; Paolucci, Luca; et al. (Clinical research in cardiology, 2025)
OBJECTIVES: INCORPORATE trial was designed to evaluate whether default coronary-angiography (CA) and ischemia-targeted revascularization is superior compared to a conservative approach for patients with treated critical limb ischemia (CLI). Registered at clinicaltrials.gov (NCT03712644) on October 19, 2018. BACKGROUND: Severe peripheral artery disease is associated with increased cardiovascular risk and poor outcomes. METHODS: INCORPORATE was an open-label, prospective 1:1 randomized multicentric trial that recruited patients who had undergone successful CLI treatment. Patients were randomized to either a conservative or invasive approach regarding potential coronary artery disease (CAD). The conservative group received optimal medical therapy alone, while the invasive group had routine CA and fractional flow reserve-guided revascularization. The primary endpoint was myocardial infarction (MI) and 12-month mortality. RESULTS: Due to COVID-19 pandemic burdens, recruitment was halted prematurely. One hundred eighty-five patients were enrolled. Baseline cardiac symptoms were scarce with 92% being asymptomatic. Eighty-nine patients were randomized to the invasive approach of whom 73 underwent CA. Thirty-four percent had functional single-vessel disease, 26% had functional multi-vessel disease, and 90% achieved complete revascularization. Conservative and invasive groups had similar incidences of death and MI at 1 year (11% vs 10%; hazard ratio 1.21 [0.49-2.98]). Major adverse cardiac and cerebrovascular events (MACCE) trended for hazard in the Conservative group (20 vs 10%; hazard ratio 1.94 [0.90-4.19]). In the per-protocol analysis, the primary endpoint remained insignificantly different (11% vs 7%; hazard ratio 2.01 [0.72-5.57]), but the conservative approach had a higher MACCE risk (20% vs 7%; hazard ratio 2.88 [1.24-6.68]). CONCLUSION: This trial found no significant difference in the primary endpoint but observed a trend of higher MACCE in the conservative arm.
Keywords: Male; koronární angiografie; Treatment Outcome; lidé středního věku; ischemie; Prospective Studies; Critical limb ischemia; nemoci koronárních tepen; Humans; Peripheral Arterial Disease; Middle Aged; senioři; prospektivní studie; mužské pohlaví; Female; Fractional flow reserve; Coronary Artery Disease; Aged; Coronary artery disease; ženské pohlaví; Coronary angiography; onemocnění periferních arterií; konzervativní terapie; Coronary Angiography; Ischemia; lidé; Conservative Treatment; výsledek terapie